Our men are grinding out: a qualitative examination of sex ratio imbalances, relationship power, and low-income African American women's health. - Bontempi, Jean M Breny; Eng, Eugenia; Quinn, Sandra Crouse (Women & health, 2008)
In the United States, the number of HIV/AIDS cases among women of color is increasing, with African American women now comprising 60% of all female AIDS cases. Scholars have attributed this imbalance to social factors. The aim of this study was to explore the impact that relationship power has on heterosexual women's ability to practice safer sex. Five focus groups were conducted with 24 African American women, aged 18-57 years, residing in public housing in rural North Carolina over a six-month period in 2000. Findings suggest that women maintain their independence, despite inequities in relationship power and remain strong to make a better life for their families. Recommendations are made to promote and build upon this social identity that women have in order to help them practice healthier behaviors.
Keywords: Adult; African Americans; Anecdotes as Topic; Cultural Characteristics; Female; Focus Groups; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Middle Aged; North Carolina; Poverty; Power (Psychology); Questionnaires; Safe Sex; Sexual Behavior; Sexual Partners; Women's Health